2017
DOI: 10.24263/2310-1008-2017-5-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on chemical composition and consumer acceptability of cocoyam (colocasia esculentus) elubo

Abstract: Materials and methods: Fresh taro tubers were processed into elubo using traditional method of four treatments (P 50 S 12; P 50 S 24; P 60 S 12 and P 60 S 24 ) from parboiling at 50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…There was no significant difference (p>0.05) in the fibre content of the paste from the three cocoyam varieties. The values are comparable with those of Karim, et al, (2017) for fresh cocoyam elubo (2.30%) and boiled cocoyam elubo (3.80 to 3.83%). The inclusion of fibre in the diet is critical to human nutrition and contributes to maintaining a healthy peristaltic movement (Akinyele and Oloruntoba, 2013).…”
Section: Discussion Of Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…There was no significant difference (p>0.05) in the fibre content of the paste from the three cocoyam varieties. The values are comparable with those of Karim, et al, (2017) for fresh cocoyam elubo (2.30%) and boiled cocoyam elubo (3.80 to 3.83%). The inclusion of fibre in the diet is critical to human nutrition and contributes to maintaining a healthy peristaltic movement (Akinyele and Oloruntoba, 2013).…”
Section: Discussion Of Findingssupporting
confidence: 83%
“…In terms of variety, Xanthosoma sagittifolium had higher carbohydrate contents than the other two varieties. The values for the carbohydrate content of the flour samples compares with that of Karim et al, (2017) who reported values between 40.90 and 79.68% for pounded and steeped cocoyam flour.…”
Section: Discussion Of Findingssupporting
confidence: 58%
“…Abulude and Ojediran [14] supplemented yam flour (elubo) with soybean flour in 2006, and Barine and Frankline [15] produced composite flour from a blend of yam and African yam beans ((Sphenostylis stenocarpa)), both for amala preparation. Reports exist in the literature on the use of cocoyam and cocoyam-cowpea flour blends for preparation of amala [16,17]; paucity of information on the use of cocoyam flour blended with soybean seeds at varying proportions necessitated this study. In this report, amala was made from a blend of cocoyam flour and soy flour, and the amala dumpling made from it was evaluated.…”
Section: Introductionmentioning
confidence: 99%